Spherical detonation waves of the Chapman–Jouguet combustion model. (May 2020) - Xie, Sisi; Lai, Geng
Abstract: The study of spherically symmetric motion is important for the theory of explosion waves. In this paper, we construct rigorously self-similar detonation wave solutions to a Riemann initial–boundary value problem for the spherically symmetric Chapman–Jouguet combustion model. We give a detailed analysis to show that the problem does not have a strong detonation wave solution but has a Chapman–Jouguet detonation wave solution. We also obtain detailed structures of the Chapman–Jouguet detonation wave solution besides the existence.